Charge-reversal silver clusters for targeted bacterial killing. Issue 19 (28th April 2021) - Nie, Xuan; Gao, Fan; Wang, Fei; Liu, Cheng; You, Ye-Zi
Abstract : Ag(−)/Ag(+) clusters with negatively charged nanoparticles and big-size are transformed into positively charged nanoparticles with small size in a bacterial acidic environment to kill the bacteria effectively. Abstract : Bacterial infections have become a common global health problem, causing a wide range of properties and life loss. The development of a highly efficient, low-toxicity and targeted bacterial agent is urgently needed. As a conventional antibacterial agent, silver nanoparticles have been used for a long time, but they are still unable to achieve targeted bacterial killing. Herein, we have prepared surface positively (Ag(+) nanoparticles) and negatively (Ag(−) nanoparticles) charged silver nanoparticles by reduction of AgNO3 to construct Ag(−)/Ag(+) clusters. The zeta potential of the Ag(−)/Ag(+) nanoclusters could be controlled by changing the ratio of Ag(−) nanoparticles to Ag(+) nanoparticles. The surface negatively changed silver nanoparticles were prepared from the reaction of methyl maleic anhydride with the amino on the surface positively changed silver nanoparticles. In the acidic environment, Ag(−) nanoparticles undergo charge reversal, and Ag(−)/Ag(+) clusters with negatively charged nanoparticles and big-size are transformed into positively charged nanoparticles with small size. The in vitro experimental results demonstrate that the positively charged nanoparticles can be well adsorbed on the negatively charged bacteria, exhibiting a high bactericidal ability. Furthermore, the in vivo skin wound healing experiment showed that the Ag(−)/Ag(+) clusters could serve as an efficient antibacterial agent to combat bacterial infection.